PERAN KEPEMIMPINAN ADAT “NINIAK MAMAK” PADA PERILAKU POLITIK MASYARAKAT DI MINANGKABAU - Sari, Lusi Puspika; Havifi, Ilham (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Political behavior reflects the participation of society in the processes of political decision-making and public policy. In Minangkabau society, traditional figures such as niniak mamak are considered to play a significant role in shaping political tendencies and orientations. This influence is both symbolic and practical, mobilizing political support and influencing electoral choices. This study aims to analyze the influence of the role of niniak mamak on the political behavior of the Minangkabau people. The research employs a qualitative approach through literature studies. The findings indicate that the political behavior of the Minangkabau community is highly collective and rooted in customary traditions, influenced by traditional leadership structures, particularly niniak mamak, who are regarded as informal elites. This role is evident in election practices, local elections (pemilihan kepala daerah), customary deliberations, and decision-making processes within the customary communityKeywords: Political Behavior; Minangkabau Society; Niniak Mamak; Traditional Leadership